Driving Towards a Sustainable Future: Optimizing Electric Vehicle Utilization in Last-Mile Supply Chain Operations - Chandra, Subhash (ExcelingTech, 2024)
This is an era where environment has become one of the key concerns due to progressive deterioration caused by human activities that generate pollution. Hence it has become imperative for businesses to alter their strategies pertaining to operation and transport logistics and chose and implement more environment friendly options. Almost without exception, the logistics sector of any enterprise is the one with a significant carbon footprint, if not the largest. The growing gravity of the environmental damage has urged the enterprises to initiate a significant move towards choosing an alternative method of operation that is not only less polluting but is also a more sustainable option. This article evaluates the use of EV as a sustainable green alternative for last mile logistics and creates the scope for further research on possible alternatives.